Northampton outcome for first and second line chemotherapy in non-small cell lung cancer: 5 years data - Eldeeb, Hany; Reza, Shariar (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : There is a definite improvement of progression-free survival as well as overall survival in treating patients with non-small cell lung cancer (NSCLC) with second line chemotherapy. We reviewed the use of chemotherapy in the first and second line setting at Northampton Oncology Centre with emphasis on the survival benefit. The goal of this retrospective study was to review our clinical practice in delivering multiple lines of therapy in comparison to published data worldwide. Material and methods : Data were collected from patients’ records and the oncology database in Northampton Oncology Centre for patients with non-small cell lung cancer patients. A total of 156 patients’ records were studied. Results: Out of 156 cases, 108 (69.23%) received first line chemotherapy and 48 (30.77%) received second line chemotherapy. Average survival in the first line group was 395 days (13 months) and in the second line group it was 580 days (19 months). There was a difference of 6.1 months (p = 0.04). Also in the first group average time to progression was 8.5 months and in the second group it was 10.5 months, a difference of nearly two months. Conclusions : Although we have improved the survival of patients who have metastatic NSCLC with our first line treatments, the rate of recurrence and mortality remains high. Second line chemotherapy should be offered in a selected group of patients.